DIVERSITY OF PHYTOPLANKTONS & ZOOPLANKTONS IN SURYAPOKHRA POND (MANPUR, GAYA, INDIA) IN RELATION TO FISH CULTURE Labeo rohita & Clarias batrachus - KUMAR, PAWAN; SHARAN, NANDINI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Background: In Suryapokhra Pond, there is abundances of Phytoplanktons, Zooplanktons and fresh water fishes like Labeo rohita and Clarias batrachus. Phytoplanktons are best studied aquatic autotrophs. Four groups of algal classes of the pond Suryapokhra Gaya, namely Chlorophyceae, Cyanophyceae, bacillariophyceae and Charophyceae were studied. Chlorophyceae genera were minimum as 5 in June while maximum was 12 in December to March. Cyanophyceae genera were minimum as4 in June while maximum was 10 in December to Feb and May 2019. Bacilariophyceae genera were minimum as 4 in June & July while maximum was 7 in March & April and Charphyceae genera were minimum as 2 in May & July while maximum was 3 in rest of months. There percentage share with the population were 60, 31, 07 and 02 respectively. Objectives: A proper statistical analysis (Correlation with species and ecological factors) has been done which supports the species diversity and condition factors of fish species. The diurnal variation of planktonic production, movement of organism and other related studies with relation to changes in physico – chemical factor in freshwater bodies in tropical regions have received even lesser attention. Only a few contributins are available in case of fresh water pond and reservoirs. Notables among them are Ganapati 1995), who made several contributions reganding the diurnal fluctuation of plankton in the freshwater pond and reservoirs of south India. Results: Various ecological factors show positive and negative correlation with phytoplanktons and Zoo planktons. Various indices are important factors which show the condition factor of fish species. Conclusion: In the present investigation, attempt has been made to study the planktons production and their abundance in pond. The diversity of planktons controls fish species which are influenced by hydrobiological parameters. This is shown by statistical analysis.